Leaf morphology characterization and propagation of Cnidoscolus aconitifolius (Redonda cultivar) using different stem cutting lengths in the tropical ecosystem - FITRA GUSTIAR; BENYAMIN LAKITAN; STRAYKER ALI MUDA; ROFIQOH PURNAMA RIA; INDRA ADVENT SIMAMORA (Society for Indonesian Biodiversity, 2024)
Abstract. Gustiar F, Lakitan B, Muda SA, Ria RP, Simamora IA. 2024. Leaf morphology characterization and propagation of Cnidoscolus aconitifolius (Redonda cultivar) using different stem cutting lengths in the tropical ecosystem. Biodiversitas 25: 2836-2844. Chaya (Cnidoscolus aconitifolius (Mill.) I.M.Johnst.) is a kind of perennial vegetable known to originate from Mexico and thrive in the tropical climate of Asia, with different leaf morphology as well as several cultivars, including Redonda cv. Therefore, this study aims to assess the leaf morphology of Chaya Redonda cv. and its growth on different stem cutting lengths of 20 cm, 25 cm, and 30 cm, respectively. All treatments were repeated four times and each replication contained five plant units, while collected data included characteristics in the form of leaf length and width, area, growth rate, and yield. Based on observation through a dimensional method, the Chaya Redonda cv. leaf had a square size with the bottom and top width identical to the ratio value of length and width consistently approaching 1.0 and remaining constant across the development process. The results showed that leaf length (L2) x bottom width (W1) regression had the highest accuracy level for determining ??undamaged chaya leaf area with a coefficient of determination (R2) value of 0.9839. The potential of cuttings with a length of 30 cm was confirmed to have high growth capacity, which also produced a positive effect on leaf number and area, as well as canopy area and fresh leaf weight.